Study of Magnetic Field and Rotation on Couple-Stress in Non-Newtonian Fluids - Subhash Kumar; Dr. H. K. Pandey; Dr. K. B. Singh (International Journal of Scientific Research in Science and Technology, 2025)
In this present paper, we studied about magnetic field and rotation on couple-stress in a non-Newtonian fluids.
Keywords: Thermal Stability; Newtonian Fluid; Instability; Rotation; Magnetic Field